A study on cancer awareness among people attending a tertiary level care hospital in West Bengal - Sen Gupta, Debjani; Soma Chakrabarty; Swati Majumdar; Subhadip Dutta; Spandan Mandal (Asian Journal of Medical Sciences, 2023)
Background: A cross-sectional observational study conducted in the outpatient registration counter among people seeking registration ticket in a government Medical College. Sample size was 214 with equal representation of each sex. Aims and Objectives: (1) The study’s aims at assessing the knowledge quotient about the occurrence, site presenting symptoms risk factors and outcome of various cancers. (2) Sex specific cancer screening program self-breast examination, mammography, pap smear awareness, and usage among females of study population have been investigated. Materials and Methods: A cross-sectional observational study. Predesigned pretested questionnaire was administered to consenting participants among those registering for outpatient tickets at Calcutta National Medical college Hospital. Statistical analysis Used: Descriptive statistics was used with MS Excel. Results: Awareness was 69.8% with 69% stating gastrointestinal tract to be the most common site, Of the population 70% stated pain was to be the most common presenting symptom, tobacco was said to be the most common causative agent by 72% and 70% stated it to be non-treatable. Among sex specific cancers 40% women identified breast as site of cancer presenting with nipple discharge and 34% stated the presenting feature to be lump. Screening method of self-breast examination and PAP smear was said by 5% and 2%, respectively. Conclusion: The awareness regarding site cardinal signs outcome and risk factors was not good among study population. Much effort is to be given to address the state of things.